Credit control and interest-income reliability in a community microfinance cooperative: Evidence from a kelurahan - level PMK case - Puryani, Ari (Privietlab, 2025)
This study examines how credit control disciplines—process conformance, authorization limits, collection oversight, and accounting recognition—shape the stability of interest income in a kelurahan-level microfinance cooperative (Koperasi PMK). Using a descriptive–analytic, quantitative design with secondary financial statements, the analysis connects the cooperative’s Standard Operating Procedures (Institutional and Education SOPs) to the full credit cycle (origination, appraisal, approval, disbursement, collection, remedial) and to recognition policies for performing and non-performing loans. Findings indicate a consistent execution gap: although approval hierarchies, 5C/7C screening, and periodic reviews are formally specified, field-intensive collections and limited information systems delay risk classification and accrual suspension. The absence of a dedicated accrued-interest ledger (PYMAD) and incomplete off-balance-sheet treatment for NPLs create a bias toward overstated interest income during stress, followed by reversals. The study argues that hardening execution—not redesigning policy—yields the highest payoff: enforce status-based recognition (accrual for performing, cash basis for deteriorated), stand up PYMAD and provisioning by collectibility bucket, implement maker–checker and daily receipt–ledger reconciliations in collections, and institutionalize monthly early-warning reviews under board and supervisory oversight. These steps trade short-term reported income for durable, decision-useful interest earnings, aligning sustainability with the cooperative’s outreach mandate.